2019
DOI: 10.5334/ijc.887
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation to Climate Change in Rain-Fed Farming System in Punjab, Pakistan

Abstract: Farmers in the rain-fed agriculture in arid regions are highly exposed to the adverse effects of climate change due to complete reliance on frequency, intensity, and timing of the rainfall. Adaptation, in such condition, becomes crucial to remain in farming in climate change regime. In the rural settings of the less-developed areas, farm households mostly adapt to risks posed by climate change individually. However, the benefits of private adaptation can be private and public depending on the type of adaptatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 47 publications
0
26
0
Order By: Relevance
“…In this respect, Ndamani and Watanabe (2016) argued that better-educated farmers are more knowledgeable due to their ability to access information about climate change and adaptation options. Several studies further emphasized the importance of farming experience in increasing farmers' adaptation probability (Bakhsh and Kamran 2019;Thoai et al 2018;Tessema et al 2017;Kebede et al 1990). In contrast, some others affirmed that the possibility of adaptation is restrained by farming experience (Shiferaw and Holden 1998;Uddin et al 2014;Ndamani and Watanabe 2016).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In this respect, Ndamani and Watanabe (2016) argued that better-educated farmers are more knowledgeable due to their ability to access information about climate change and adaptation options. Several studies further emphasized the importance of farming experience in increasing farmers' adaptation probability (Bakhsh and Kamran 2019;Thoai et al 2018;Tessema et al 2017;Kebede et al 1990). In contrast, some others affirmed that the possibility of adaptation is restrained by farming experience (Shiferaw and Holden 1998;Uddin et al 2014;Ndamani and Watanabe 2016).…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, to remain effective, these strategies were required to evolve over time following the discourse of CC and society (Omerkhil et al, 2020); an approach that is similarly applicable in Nigeria. In Pakistan, Bakhsh and Kamran (2019) showed that adaptation strategies adopted by farmers involved labour-intensive farm practices such as soil bund-making, deep ploughing, and crop diversification. A variety of socioeconomic factors however influenced farmers' responses to adoption.…”
Section: Fersoy and Jorgensen (2021)mentioning
confidence: 99%
“…Climate change may reduce organic matter levels in soils and may negatively affect soil fertility through impact on carbon and nitrogen cycles (Brevik, 2013;Pahore et al, 2016) About 5 million ha of the cultivated area (24% of the total cultivated area) in Pakistan is rain-fed (GoP, 2010). Rain-fed agriculture is vulnerable to climate change as poor economic conditions of farmers and limited availability of water hamper the adoption of technological interventions (Bakhsh and Kamran, 2019). Managing soils under climatic change is a challenge for scientists across the world as well as in Pakistan.…”
Section: Impact Of Climate Change On Soil Resourcesmentioning
confidence: 99%